2015
DOI: 10.1055/s-0035-1547520
|View full text |Cite
|
Sign up to set email alerts
|

Angiosarcoma of the Head and Neck

Abstract: Introduction Angiosarcoma of the head and neck is a rare vascular sarcoma associated with high rates of local recurrence and distant metastasis and a poor prognosis. Objective We describe our experience treating patients with angiosarcoma of the head and neck to evaluate the outcomes, patterns of failure, and current treatments. Methods We identified six patients with angiosarcoma of the head and neck and treated at our institution between 2000 and 2013. We compared our results to the literature from 1979 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 24 publications
0
29
0
4
Order By: Relevance
“…According to Lim et al [ 22 ], radical resection with a sufficient safety margin (5 cm) may provide survival advantage. Up-to-date nonsurgical treatment modalities such as immunotherapy or gene therapy may be promising [ 5 , 15 , 20 ]. There are still ongoing debates about the application of chemotherapy in the standard AS treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lim et al [ 22 ], radical resection with a sufficient safety margin (5 cm) may provide survival advantage. Up-to-date nonsurgical treatment modalities such as immunotherapy or gene therapy may be promising [ 5 , 15 , 20 ]. There are still ongoing debates about the application of chemotherapy in the standard AS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This tumor predominantly develops in elderly people and more frequently affects men than women [ 2 4 ]. AS accounts for less than 2% of all cases of soft-tissue sarcoma and less than 1% of cases of head and neck cancer [ 5 7 ]. The etiology of AS has not been fully understood, but several reports have shown some positive association with chronic lymphedema [ 8 ] or prior irradiation [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using mutational signature analysis to understand the possible origins of tumor hypermutation, we 7 found that all 9 of these HNFS samples with high TMB had a dominant mutational signature representing damage from ultraviolet (UV) light (COSMIC Signature 7) 25 Figure 6D). The fact that high TMB and a concomitant dominant mutational signature of UV light exposure occurs uniquely in HNFS AS suggest a common etiologic and genomic basis for HNFS AS, which is an AS subtype accounting for nearly 60% of AS cases 26,27 .…”
mentioning
confidence: 99%
“…Cutaneous primary angiosarcoma usually develops on the face or scalp and predominantly affects elderly people, frequently men [ 8 10 ]. Choi et al [ 11 ] reported a retrospective analysis of 14 patients with angiosarcoma of the scalp and Mullins and Hackman [ 12 ] reported 5 more patients. Most of the patients in both of these studies were men, with only one woman, while the mean age was 69 and 65.5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients in both of these studies were men, with only one woman, while the mean age was 69 and 65.5 years. Both of the studies concluded that this malignancy is very aggressive, with prognosis dependent upon size and completeness of tumor excision [ 11 , 12 ]. The only case of an angiosarcoma of the scalp occurring in a pediatric patient that we found was the one described by Khan et al [ 13 ].…”
Section: Discussionmentioning
confidence: 99%